Análisis Jurídico y Doctrinario a la Sentencia sobre la vulneración del Derecho a la Consulta Ambiental del Juicio No. 11333202200183 – Caso Fierro Urco. - Bermeo Armijos, Diego Andrés (2023)
The purpose of the Protection Action is to annul judicial decisions or guarantee violated Fundamental Rights and immediately order their reparation in the face of any action or omission. The present investigation seeks to evidence the lack of commitment on the part of the institutions in charge of the care of the environment at the moment of applying the mechanisms of the Environmental Consultation and Prior Consultation, which derives in a double problematic, the supposed undue granting of registrations and environmental licenses and the supposed environmental degradation by the bad mining practices, reason why the present Work of Titling will seek to rectify the violations of the Constitutional Rights that are presented when this type of Consultations are not applied in a correct way by the corresponding organisms. The study carried out in the present analysis of the Judgment seeks to evidence the violation of the Constitutional Law to the previously mentioned legal figures. The main objective of this research is to form a legal criterion regarding the decisions made by the Civil Judicial Unit with headquarters in Loja Canton, Loja Province. In addition, we analyzed the concordant legislation on the criteria issued by the Constitutional Court of Ecuador in judgments that are similar on the matter of conflict, seeking to find if in this ruling Constitutional Rights such as the Rights of Good Living, Rights of Communities, Peoples and Nationalities, Rights of Participation and Rights of Nature were violated. In this Title Work, materials and methods were applied, by means of which the research was developed, surveys and interviews to professionals and experts of the Law were carried out, thanks to these results it was possible to analyze and propose recommendations regarding the correct application of the Environmental Consultation and Prior Consultation and consequently the correct granting of environmental registrations and licenses.